O uso do eugenol contra Aeromonas hydrophila e seu efeito sobre parâmetros hematológicos e imunológicos em jundiás (Rhamdia quelen) - Sutili, Fernando Jonas (2014)
In aquaculture, eugenol have been used and recommended as anesthetics for several fish species. Moreover, this product has attracted the attention of researchers because of its chemopreventive, anti-inflammatory and antioxidant properties, as well as, its antimicrobial potential. The aim of this study was to evaluate the activity of eugenol against the fish pathogen Aeromonas hydrophila and eugenol s effect on hematological and natural immune parameters in silver catfish (Rhamdia quelen). In vitro, eugenol showed weak activity against A. hydrophila, but in vivo, at a subinhibitory concentration (10 mg L-1), it promoted survival in infected silver catfish. Eugenol (50 μg mL-1) reduced the hemolytic activity of A. hydrophila supernatant in vitro in fish erythrocytes. Subjecting catfish to eugenol baths (5 and 10 mg L-1) for five days did not alter the hematological and immunological parameters studied in this work. Based on these results, eugenol can be used to treat or prevent bacterial diseases in fish.